Multifunctional Stretchable Conductive Woven Fabric Containing Metal Wire with Durable Structural Stability and Electromagnetic Shielding in the X-Band - Wang, Yong; Gordon, Stuart; Baum, Thomas; Xu, Zhenzhen (Polymers, 2020)
Elastomeric, conductive composite yarns have recently received attention around the opportunity for them to offer special protective fields. A straightforward approach for fabricating tri-component elastic-conductive composite yarns (t-ECCYs) containing stainless steel wire (SSW) was proposed previously. This work mainly focuses on the electromagnetic shielding effectiveness (EMSE) of weft-stretchable woven fabric containing t-ECCY over the X-band under different testing conditions, e.g., single step-by-step elongation, cyclic stretch and lamination events. Results showed that a woven cotton fabric with weft yarn of t-ECCY not only exhibited superior weft stretch-ability to a higher elongation (>40%) compared with a pure cotton control but also had an acceptable 15-cyclic stability with 80% shape recovery retention. The t-ECCY weft fabric was effective in shielding electromagnetic radiation, and its EMSE was also enhanced at elevated elongations during stretch at parallel polarization of EM waves. There was also no decay in EMSE before and after the t-ECCY fabric was subject to 15 stretch cycles at extension of 20%. In addition, a 90° by 90° cross lamination of t-ECCY fabric remarkably improved the EMSE compared to a 0°/90° one. The scalable fabrication strategy and excellent EMSE seen in t-ECCY-incorporated fabrics represent a significant step forward in protective fields.